Wide spectrum of developmental brain disorders from megalencephaly to focal cortical dysplasia and pigmentary mosaicism caused by mutations of MTOR - Mirzaa, Ghayda M. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly (HMEG) and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. Collectively, these disorders are associated with significant childhood morbidity and mortality. FCD, in particular, represents the most frequent cause of intractable focal epilepsy in children. OBJECTIVE: To identify the underlying molecular etiology of FCD, HMEG, and diffuse megalencephaly. DESIGN, SETTING AND PARTICIPANTS: We performed whole exome sequencing (WES) on eight children with FCD or HMEG using standard depth (~50-60X) sequencing in peripheral samples (blood, saliva or skin) from the affected child and their parents, and deep (~150-180X) sequencing in affected brain tissue. We used both targeted sequencing and WES to screen a cohort of 93 children with molecularly unexplained diffuse or focal brain overgrowth (42 with FCD-HMEG, and 51 with diffuse megalencephaly). Histopathological and functional assays of PI3K-AKT-MTOR pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: We identified low-level mosaic mutations of MTOR in brain tissue in four children with FCD type 2a with alternative allele fractions ranging from 0.012–0.086. We also identified intermediate level mosaic mutation of MTOR (p.Thr1977Ile) in three unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin that resembles hypomelanosis of Ito. Finally, we identified a constitutional de novo mutation of MTOR (p.Glu1799Lys) in three unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in two children with FCD type 2a from whom multiple affected brain tissue samples were available revealed a gradient of alternate allele fractions with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTORC1 and enlarged neuronal size, establishing a link between the MTOR mutations and neuronal hypertrophy found in patients. The mTORC1 inhibitor RAD001 ameliorated these phenotypes. CONCLUSIONS AND RELEVANCE: Our data show that mutations of MTOR are associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2 to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations are sufficient to cause cellular hypertrophy in cultured neurons. Our data also provide a compelling demonstration of the pattern of mosaicism in brain, and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.